Postural balance and oculomotor control are influenced by neck kinaesthetic functions in elite ice hockey players - Rosker, Z. M.; Kristjansson, E.; Vodicar, M.; Rosker, J. (Gait and Posture, 2021)
Background: Research indicates that neck kinaesthetic awareness plays an important role in oculomotor and balance control, however the relationship has not been studied in athletes. As performance in ice hockey demands visual perception acuity during skating, while constantly shifting between unilateral and bilateral stances in sports specific posture more in-depth relationship should be studied. Research question: What is the relationship between neck kinaesthetic awareness, postural balance and eye movement control in professional ice hockey players and non-trained individuals? Methods: In this observational study, centre-of-pressure was measured using force plate in twenty-eight hockey players and thirty non-trained participants during different stances in eyes-opened and eyes-closed conditions. Butterfly test and Head-to-Neutral Relocation test were performed to assess neck kinaesthesia. Horizontal smooth pursuit eye movements were measured using video-oculography. Linear regression was used to determine the relationship between neck kinaesthesia, body sway and oculomotor control. Results: Time-on-target in Butterfly test was able to predict low to medium proportions of variance in amplitude and velocity parameters for single leg stances in hockey players (R2 = .220-.698). Head-to-Neutral Relocation test was able to predict low to medium proportion of variance in average eye movement velocity during first 100 milliseconds of smooth pursuit initiation for both groups (R2 = .262-.541). Significance: Findings from our study suggest that cervical spine afferent input plays an important role in maintaining unilateral postural balance in hockey players, with less evidence presented in controls. Sports specific posture or upper body loading could lead to adaptations in neck proprioception, not frequently considered when searching for balance related injury risk factors or performance deficits. Our study suggests, that in addition to balance control, neck kinaesthesia can also affect oculomotor performance which was present in both groups. This is especially evident when initiating changes in eye movement direction